High-Performance Government Structure, Leadership, Incentives - Klitgaard, Robert (RAND Corporation, 2005)
In 2003, the National Commission on the Public Service, chaired by Paul Volcker, issued a report detailing problems within the federal government today and recommending changes in its organization, leadership, and operations. This book suggests practical ways to implement the recommendations and defines a research agenda for the future. Thirteen essays address the primary problem areas identified by the Volcker Commission, and the commission report itself is included.